The Effect of Empowering Leadership, Employee Development, and Personality Traits on Employee Engagement PTA - Evelina Debora Damanik; Moch Asmawi; IGK Agung Ulupui (Green Publisher Indonesia, 2022)
This study aims to obtain an overview of employee engagement level at PTA and examine the influence of leadership factors, particularly empowering leadership, employee development, and personality traits on employee engagement in the company. The research was designed using a quantitative approach with a correlational type of research, while the research sample was selected using a purposive sampling technique. Data collection was carried out using questionnaires compiled with a Likert scale. Furthermore, the statistical data obtained were analyzed using the Structural Equation Modeling Partial Least Square (SEM-PLS) approach using the SmartPLS application (v.3.2.9). The results showed that the predictive accuracy level of the structural model of this study was categorized as moderate (Adjusted R2 = 0.428, referring to Chin, 1998). It also represents the total variance of employee engagement variables that can be explained by all exogenous variables simultaneously, which is 42.8%, and 57.2% influenced by other variables that were not discussed in this research model. The three exogenous variables were found positively affect employee engagement. The personality traits factor has a more significant influence than other variables (0.362). The following factor is employee development (0.241), and the slightest effect is empowering leadership (0.231).